INNOVATIVE DEVELOPMENT INUZBEKISTAN: THE CHINESE EXPERIENCE - Mirzaev Kulmamat Djanzakovich (Western European Studies, 2024)
This article discusses issues of innovative development of digitalization issues in the conditions of Uzbekistan based on the experience of China
Keywords: technology; method; style; development